1-Chloromethyl-3-nitrobenzene - Abbasi, Muhammad Athar (International Union of Crystallography, 2010)
In the title molecule, C(7)H(6)ClNO(2), the plane of the nitro group and the direction of the chloromethyl group are twisted away from the benzene ring, forming dihedral angles of 8.2 (3) and 67.55 (12)°, respectively. In the crystal structure, weak intermolecular C—H⋯O interactions link the molecules into corrugated sheets parallel to the bc plane.